The spite house / A Novel - Compton, Johnny (New York : Nightfire, Tor Publishing Group, 2023)
"A terrifying Gothic thriller about grief and death and the depths of a father's love, Johnny Compton's The Spite House is a stunning debut by a horror master in the making--The Babadook meets A Headful of Ghosts in Texas Hill Country. Eric Ross is on the run from a mysterious past with his two daughters in tow. Having left his wife, his house, his whole life behind in Maryland, he's desperate for money--it's not easy to find steady, safe work when you can't provide references, you can't stay in one place for long, and you're paranoid that your past is creeping back up on you. When he comes across the strange ad for the Masson House in Degener, Texas, Eric thinks they may have finally caught a lucky break. The Masson property, notorious for being one of the most haunted places in Texas, needs a caretaker of sorts. The owner is looking for proof of paranormal activity. All they need to do is stay in the house and keep a detailed record of everything that happens there. Provided the house's horrors don't drive them all mad, like the caretakers before them. The job calls to Eric, not just because there's a huge payout if they can make it through, but because he wants to explore the secrets of the spite house. If it is indeed haunted, maybe it'll help him understand the uncanny power that clings to his family, driving them from town to town, making them afraid to stop running"--
"A novel"--Cover.
Keywords: Haunted houses -- Fiction; Divorced men -- Fiction; Fathers and daughters -- Fiction; Psychics -- Fiction; Parapsychology -- Fiction; Landlord and tenant -- Fiction; Texas -- Fiction; Ghost stories; Horror fiction; Gothic fiction; Horror fiction; Ghost stories; Horror fiction; Gothic fiction; Novels